1987
DOI: 10.1139/f87-226
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Divergence and the Organization of Trophic Characters Among Lacustrine Populations of the Threespine Stickleback (Gasterosteus aculeatus)

Abstract: A multivariate solution for dealing with patterns of character covariance, when character genotypic covariances are known, has been applied to the organization of trophic morphology among lacustrine populations of the threespine stickleback (Gasterosteus aculeatus). The quantitative genetics governing eight trophic characters were investigated using representative populations from each of three known trophic ecotypes (open-water, littoral, and intermediate) which occur in the same drainage. Character heritabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…The average heritability reported for morphometric characteristics of chum salmon ranged between 0.3 and 0.6, depending on rearing temperature (Beacham 1990). Lavin and McPhail (1987) reported heretabilities between 0.19 and 0.84 for morphometric characteristics in the threespine stickleback G. aculeatus. Grudzien and Turner (1984) reported a heritability of 0.44 for the mouth width polymorphism in Ilyodon.…”
Section: Genetic Influencesmentioning
confidence: 92%
“…The average heritability reported for morphometric characteristics of chum salmon ranged between 0.3 and 0.6, depending on rearing temperature (Beacham 1990). Lavin and McPhail (1987) reported heretabilities between 0.19 and 0.84 for morphometric characteristics in the threespine stickleback G. aculeatus. Grudzien and Turner (1984) reported a heritability of 0.44 for the mouth width polymorphism in Ilyodon.…”
Section: Genetic Influencesmentioning
confidence: 92%
“…often corresponds with a change in behaviour, including strategies of feeding (e.g. Lavin & McPhail 1987), predator defense (e.g. Bronmark & Miner 1992) and territoriality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson and Wilson (1994) provide such evidence by stating that genetic differentiation is linked to phenotypic differences in 19 of 48 lacustrine fish species. Moreover, McPhail (1984 and Lavin and McPhail (1987) have demonstrated that phenotypic differences between benthic and pelagic forms of sticklebacks persist when different morphs are cultured in the laboratory and provided with the same diet.…”
Section: Implications For Alpha-level Taxonomymentioning
confidence: 99%